2012
DOI: 10.1105/tpc.112.100214
|View full text |Cite
|
Sign up to set email alerts
|

The Time Required for Dormancy Release in Arabidopsis Is Determined by DELAY OF GERMINATION1 Protein Levels in Freshly Harvested Seeds

Abstract: Seed dormancy controls the start of a plant's life cycle by preventing germination of a viable seed in an unfavorable season. Freshly harvested seeds usually show a high level of dormancy, which is gradually released during dry storage (afterripening). Abscisic acid (ABA) has been identified as an essential factor for the induction of dormancy, whereas gibberellins (GAs) are required for germination. The molecular mechanisms controlling seed dormancy are not well understood. DELAY OF GERMINATION1 (DOG1) was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
388
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 210 publications
(410 citation statements)
references
References 65 publications
14
388
1
1
Order By: Relevance
“…Further support for our conclusion that the L. papillosum 34-kD antigens in Figures 6 and 7 are indeed the LepaDOG1 proteins comes from an interesting observation of Nakabayashi et al (2012). Those authors demonstrated that the AtDOG1 proteins with a calculated molecular mass of approximately 32 kD exhibit significantly slower SDS-PAGE migration (i.e.…”
Section: Analysis Of L Papillosum Dog1 Protein Expression During Seesupporting
confidence: 62%
See 4 more Smart Citations
“…Further support for our conclusion that the L. papillosum 34-kD antigens in Figures 6 and 7 are indeed the LepaDOG1 proteins comes from an interesting observation of Nakabayashi et al (2012). Those authors demonstrated that the AtDOG1 proteins with a calculated molecular mass of approximately 32 kD exhibit significantly slower SDS-PAGE migration (i.e.…”
Section: Analysis Of L Papillosum Dog1 Protein Expression During Seesupporting
confidence: 62%
“…5). Furthermore, we detected transcripts of LepaDOG1a and LepaDOG1c in L. papillosum seeds, a transcript origin also evident for the putative Brassicaceae orthologs LesaDOG1, BrDOG1, and AtDOG1 in L. sativum, B. rapa, and Arabidopsis, respectively (Bentsink et al, 2006;Graeber et al, 2010;Footitt et al, 2011;Nakabayashi et al, 2012). The genomic sequences of LepaDOG1a and LesaDOG1 show more than 80% similarity with highly similar exon regions and, due to conserved splice sites, more than 98% putative amino acid sequence similarity despite rather diverging intron sequences.…”
Section: Discussion Spatiotemporal Maturation Patterns In L Papillosmentioning
confidence: 85%
See 3 more Smart Citations